Pelaporan Keuangan pada UMKM di Surabaya (Studi Pada UKM Diah Cookies) - Titis Puspitaningrum; Sri Lestari Kurniawati; Nosy Yodi Metana (Universitas Pendidikan Nasional, 2017)
ABSTRACT Financial reports become one of absolute components that must be possessed by Small and Medium Enterprise (SME) as the requirement to develop business by proposing capital to the bank as the creditors. As a result, the habit of recording every business activity occurred and arranging financial report should be grown among SME. Therefore, this study attempts to put forward the importance of growing habit of recording and arranging financial report for SME in accordance to accounting standard but still using easily practical format, which is by using computerized records.The method used in this study was qualitative. The purpose of this study is to analyze the extent to which SME applies its recording of financial report as well as provide training in making bookkeeping systematically by using computer program, that is excel program. Qualitative is the type used in this study to analyze SME Diah Cookies in Surabaya. This SME is engaged in the manufacture of pastries. Based on the writer’s observation with Mrs. Diah, the owner of SME, Diah Cookies, she is able to explain the definition, interpret, and give example of the picture related to the names of the account contained in the financial reports yet only limited to capital, profit/loss, and property. The informants has done the recording despite in the simple form and also able to interpret, distinguish, and explain. They have not been able to understand by the level of exploration where business actors can estimate. However, with the additional knowledge delivered by research team based on computerized bookkeeping, SME Diah Cookies has started to carry out bookkeeping by using excel program. Key words: UKM, Financial Report